Sulfide-based solid electrolyte and all-solid-state lithium ion battery

By replacing phosphorus with silicon in Li4PS4I and replacing sulfur with larger halogen, the sulfide-based solid electrolyte of Li4P1-xSixS4-xHaxI was formed, and the problem of low conductivity of Li4PS4I was solved, and the battery capacity of all-solid-state lithium-ion batteries was improved.

CN119744423APending Publication Date: 2025-04-01JX NIPPON MINING & METALS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380061051.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-17
Filing Date
2023-05-25
Publication Date
2025-04-01

Smart Images

  • Figure CN119744423A_ABST
    Figure CN119744423A_ABST
Patent Text Reader

Abstract

Provided are: a sulfide-based solid electrolyte having good ionic conductivity; and an all-solid-state lithium ion battery using the sulfide-based solid electrolyte. The sulfide-based solid electrolyte is represented by the compositional formula: Li4P1-xSixS4-xHaxI (in the formula, Ha is any one or two of Cl, Br and I, and 0.05 < x < = 0.3).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a sulfide-based solid electrolyte and an all-solid-state lithium-ion battery. Background Art

[0002] In recent years, with the rapid popularization of information-related equipment, communication equipment, etc. such as personal computers, cameras and portable phones, the development of batteries used as their power sources has received attention. Among these batteries, lithium-ion batteries have received attention from the viewpoint of high energy density. In addition, lithium-ion secondary batteries used in large-scale applications such as power sources for vehicle-mounted use and load leveling also require high energy density and improved battery characteristics.

[0003] However, in the case of lithium-ion batteries, the electrolyte is mostly organic compounds, and even if flame-retardant compounds are used, it cannot be asserted that there is no risk of fire. As an alternative to such liquid lithium-ion batteries, all-solid-state lithium-ion batteries with solid electrolytes have attracted much attention in recent years. Among them, all-solid-state lithium-ion batteries with sulfides such as Li2S-P2S5 and lithium halides added thereto as solid electrolytes are becoming mainstream.

[0004] Li4PS4I, a sulfide, is a tetragonal Li ion conductor with a space group of P4 / nmm. Since it is electrochemically stable and produces little H2S when exposed to the atmosphere, it is expected to be a candidate for a solid electrolyte for all-solid-state batteries as the next generation of Li ion batteries. In non-patent document 1, a material such as Li4PS4I was discovered by a solvent-based synthesis method, and the crystal structure of the material was clarified.

[0005] Prior art literature

[0006] Non-patent literature

[0007] Non-patent document 1: Stefan J. Sedlmaier et al., Li4PS4I: A Li+Superionic Conductor Synthesized by a Solvent-Based Soft Chemistry Approach, Chem. Mater. (2017), 29, 1830-1835. Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, the Li ion conductivity of Li4PS4I is 1.2×10 -4S / cm, which is about 1 to 2 orders of magnitude lower than other materials as a sulfide-based solid electrolyte. In order to be applied to all-solid-state batteries, it is expected that the ionic conductivity will be further improved.

[0010] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a sulfide-based solid electrolyte having good ion conductivity and an all-solid-state lithium-ion battery using the sulfide-based solid electrolyte.

[0011] Solutions for solving problems

[0012] The present invention completed based on the above findings is, in one embodiment, a sulfide-based solid electrolyte having a composition formula: Li4P 1-x Si x S 4-x Ha x I (wherein Ha is any one or two of Cl, Br and I, 0.05<x≤0.3).

[0013] In another embodiment of the sulfide-based solid electrolyte of the present invention, in the above formula, 0.1≤x≤0.3.

[0014] In still another embodiment, the present invention is an all-solid-state lithium-ion battery, comprising: a solid electrolyte layer including the sulfide-based solid electrolyte of the embodiment of the present invention, a positive electrode layer, and a negative electrode layer.

[0015] Effects of the Invention

[0016] According to the present invention, a sulfide-based solid electrolyte having good ion conductivity and an all-solid-state lithium-ion battery using the sulfide-based solid electrolyte can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of an all-solid-state lithium-ion battery according to an embodiment of the present invention. DETAILED DESCRIPTION

[0018] Next, specific embodiments of the present invention will be described in detail with reference to the accompanying drawings. The present invention is not limited to the following embodiments, and it should be understood that appropriate design changes and improvements can be made based on common sense of those skilled in the art without departing from the scope of the present invention.

[0019] (Sulfide-based solid electrolyte)

[0020] The sulfide-based solid electrolyte of the embodiment of the present invention has a composition formula: Li4P 1-x Si x S 4-x Ha xI (where Ha is any one or two of Cl, Br and I, 0.05<x≤0.3). With regard to the sulfide-based solid electrolyte of the embodiment of the present invention, by replacing phosphorus (P) in the solid electrolyte with silicon (Si) having a larger ionic radius, the lattice expands and the ionic conductivity improves. In addition, by replacing sulfur (S) with any one or two of the halogens having a large ionic radius, namely Cl, Br and I, the stability of the crystal structure becomes higher, and the generation of impurity phases other than the Li4PS4I phase is suppressed. According to such a structure, the substances that hinder ionic conductivity are reduced, so that a sulfide-based solid electrolyte with good ionic conductivity can be obtained.

[0021] In the above composition formula of the sulfide-based solid electrolyte of the embodiment of the present invention, if x is less than 0.05, the amount of substitution is small, so the expansion effect of the lattice is weak, and a sufficient ion conductivity improvement effect cannot be obtained. In addition, if x is greater than 0.3, it is possible to produce Li2S phase and LiI phase with low ion conductivity. In the above composition formula of the sulfide-based solid electrolyte of the embodiment of the present invention, preferably 0.1≤x≤0.3. According to such a structure, a sulfide-based solid electrolyte with better ion conductivity can be obtained. When the ion conductivity of the sulfide-based solid electrolyte is good in this way, the voltage drop (IR drop) during discharge becomes smaller, so the battery capacity of the all-solid-state lithium-ion battery using the sulfide-based solid electrolyte becomes higher. In addition, this effect becomes significant particularly when the all-solid-state lithium-ion battery is at a high rate.

[0022] The average particle size of the sulfide-based solid electrolyte according to the embodiment of the present invention is not particularly limited, and may be 0.01 to 100 μm, 0.1 to 100 μm, or 0.1 to 50 μm.

[0023] The ion conductivity of the sulfide-based solid electrolyte according to the embodiment of the present invention is preferably 0.5 mS / cm or more, more preferably 0.8 mS / cm or more, and further preferably 1.0 mS / cm or more at 30° C. The ion conductivity of the sulfide-based solid electrolyte can be measured, for example, by the following method.

[0024] First, 0.2 g of the powder of the sulfide-based solid electrolyte is pressed at a pressure of 370 MPa to form a plate, and then 0.1 g of gold powder is spread on each side and pressed at 555 MPa to make particles with a diameter of 10 mm and a gold electrode. Using the particles, an applied voltage of 100 mV is set at 30°C, and an E4990A manufactured by TOYO Technica Co., Ltd. with open-circuit-short-circuit correction is used to perform an AC impedance measurement of 20 Hz to 100 MHz. The arc observed in the portion with a frequency of more than 10 kHz of the Cole-Cole plot obtained by the AC impedance measurement is analyzed to determine the transfer resistance of Li ions. Next, based on the following formula, the ionic conductivity is determined according to the transfer resistance of the Li ions and the thickness and area of ​​the solid electrolyte portion of the particles used in the measurement.

[0025] Ionic conductivity (mS / cm) = thickness of the solid electrolyte part of the particle (cm) × 1000 / [(Li ion transfer resistance (Ω)) × (area of ​​the solid electrolyte part of the particle (cm) 2 ))]

[0026] (Method for producing sulfide-based solid electrolyte)

[0027] Next, a method for producing a sulfide-based solid electrolyte according to an embodiment of the present invention will be described.

[0028] First, raw materials are weighed in a glove box with an inert gas atmosphere such as argon or nitrogen to obtain a predetermined composition. Examples of the raw materials used here include Li2S, P2S5, SiS2, LiCl, LiBr, and LiI.

[0029] Next, the mixture is mixed for 5 to 30 minutes using a mortar or the like to prepare a mixed powder. At this time, it is preferred that the mixed powder be mixed only for a time period such that the average particle size of the mixed powder becomes 5 to 40 μm.

[0030] Next, the mixed powder is made into granules, which are vacuum sealed in a quartz ampoule, and the entire quartz ampoule is fired at 400 to 800° C. for 1 to 20 hours, thereby producing a granular material having a composition formula of: Li4P 1-x Si x S 4-x Ha x The sulfide-based solid electrolyte according to the embodiment of the present invention is represented by I (wherein Ha is any one or two of Cl, Br and I, and 0.05<x≤0.3).

[0031] (All-solid-state lithium-ion battery)

[0032] The solid electrolyte layer is formed by the sulfide-based solid electrolyte of the embodiment of the present invention, and an all-solid-state lithium-ion battery including the solid electrolyte layer, the positive electrode layer and the negative electrode layer can be manufactured. The positive electrode layer and the negative electrode layer constituting the all-solid-state lithium-ion battery of the embodiment of the present invention are not particularly limited, and can be formed of known materials, and can be set as follows: Figure 1 The known structure shown.

[0033] The positive electrode layer of the lithium ion battery is a positive electrode composite material formed into a layer by mixing a known positive electrode active material for lithium ion batteries with the sulfide-based solid electrolyte of the embodiment of the present invention or other sulfide-based solid electrolytes.

[0034] The positive electrode composite material may further include a conductive aid. As the conductive aid, a carbon material, a metal material or a mixture thereof may be used. The conductive aid may, for example, also include at least one element selected from the group consisting of carbon, nickel, copper, aluminum, indium, silver, cobalt, magnesium, lithium, chromium, gold, ruthenium, platinum, beryllium, iridium, molybdenum, niobium, osmium, rhodium, tungsten and zinc. The conductive aid is preferably a carbon single substance with high conductivity; a metal single substance, mixture or compound containing carbon, nickel, copper, silver, cobalt, magnesium, lithium, ruthenium, gold, platinum, niobium, osmium or rhodium. As a carbon material, for example, carbon black such as Ketjen black, acetylene black, DENKA BLACK, thermal black, channel black, graphite, carbon fiber, activated carbon, etc. can be used.

[0035] The average thickness of the positive electrode layer of the lithium ion battery is not particularly limited and can be appropriately designed according to the purpose. The average thickness of the positive electrode layer of the lithium ion battery can be, for example, 1 μm to 100 μm, or 1 μm to 10 μm.

[0036] The method for forming the positive electrode layer of the lithium ion battery is not particularly limited and can be appropriately selected according to the purpose. Examples of the method for forming the positive electrode layer of the lithium ion battery include sputtering using a target of a positive electrode active material and compression molding of the positive electrode active material.

[0037] The negative electrode layer of the lithium ion battery may also be a layered negative electrode layer of a known negative electrode active material for a lithium ion battery. In addition, the negative electrode layer may also be a layered negative electrode composite material formed by mixing a known negative electrode active material for a lithium ion battery with a sulfide-based solid electrolyte or other sulfide-based solid electrolyte according to an embodiment of the present invention.

[0038] The negative electrode layer, like the positive electrode layer, may also contain a conductive aid. The conductive aid may be the same material as that described in the positive electrode layer. As the negative electrode active material, for example, a carbon material may be used, specifically, artificial graphite, graphite carbon fiber, resin-sintered carbon, pyrolysis vapor-grown carbon, coke, mesocarbon micro-beads (MCMB: mesocarbon micro-beads), furfuryl alcohol resin-sintered carbon, polyphenylene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and difficult-graphitizable carbon, or a mixture thereof. In addition, as the negative electrode material, for example, metals such as lithium metal, indium metal, aluminum metal, and silicon metal themselves, or alloys formed by combining with other elements or compounds may be used.

[0039] The average thickness of the negative electrode layer of the lithium ion battery is not particularly limited and can be appropriately selected depending on the purpose. The average thickness of the negative electrode layer of the lithium ion battery can be, for example, 1 μm to 100 μm, or 1 μm to 10 μm.

[0040] There is no particular limitation on the method for forming the negative electrode layer of the lithium ion battery, and it can be appropriately selected according to the purpose. As the method for forming the negative electrode layer of the lithium ion battery, for example, sputtering using a target material of a negative electrode active material, or a method of compression molding the negative electrode active material, a method of vapor deposition of the negative electrode active material, etc. can be listed.

[0041] The average thickness of the solid electrolyte layer of the lithium ion battery formed of the sulfide-based solid electrolyte of the embodiment of the present invention is not particularly limited and can be appropriately designed according to the purpose. The average thickness of the solid electrolyte layer of the lithium ion battery can be, for example, 50 μm to 500 μm, or 50 μm to 100 μm.

[0042] The method for forming the solid electrolyte layer of the lithium ion battery is not particularly limited and can be appropriately selected according to the purpose. Examples of the method for forming the solid electrolyte layer of the lithium ion battery include sputtering using a solid electrolyte target or compression molding of the solid electrolyte.

[0043] Other members constituting the lithium ion battery are not particularly limited and may be appropriately selected depending on the intended purpose. Examples thereof include a positive electrode current collector, a negative electrode current collector, and a battery case.

[0044] The size and structure of the positive electrode current collector are not particularly limited and may be appropriately selected depending on the intended purpose.

[0045] Examples of the material of the positive electrode current collector include die steel, stainless steel, aluminum, aluminum alloy, titanium alloy, copper, gold, and nickel.

[0046] Examples of the shape of the positive electrode current collector include a foil shape, a plate shape, and a mesh shape.

[0047] The average thickness of the positive electrode current collector may be, for example, 10 μm to 500 μm, or 50 μm to 100 μm.

[0048] The size and structure of the negative electrode current collector are not particularly limited and may be appropriately selected depending on the intended purpose.

[0049] Examples of the material of the negative electrode current collector include die steel, gold, indium, nickel, copper, and stainless steel.

[0050] Examples of the shape of the negative electrode current collector include a foil shape, a plate shape, and a mesh shape.

[0051] The average thickness of the negative electrode current collector may be, for example, 10 μm to 500 μm, or 50 μm to 100 μm.

[0052] There is no particular limitation on the battery case, and it can be appropriately selected according to the purpose, and for example, known laminated films that can be used in existing all-solid-state batteries can be listed. As laminated films, for example, laminated films made of resin, films formed by vapor deposition of metal on laminated films made of resin, etc. can be listed.

[0053] The shape of the battery is not particularly limited and may be appropriately selected depending on the intended purpose. Examples thereof include cylindrical, rectangular, button, coin, and flat shapes.

[0054] Example

[0055] Hereinafter, examples are provided for better understanding of the present invention and its advantages, but the present invention is not limited to these examples.

[0056] (Example 1)

[0057] In an argon atmosphere glove box, the raw material was charged to form Li4P 0.9 Si 0.1 S 3.9 Cl 0.1 The raw materials were weighed in the manner of I and mixed in a mortar for 15 minutes to prepare a mixed powder. Next, the mixed powder was made into 1 g of pellets, which were vacuum sealed in a quartz ampoule, and the entire quartz ampoule was calcined at 500°C for 8 hours to obtain a Li4P 0.9 Si 0.1 S 3.9 Cl 0.1 A sulfide-based solid electrolyte having a composition of I.

[0058] (Example 2)

[0059] The raw material charge composition is Li4P 0.8 Si 0.2 S3.8 Cl 0.2 I, except for this, the same implementation as in Example 1.

[0060] (Example 3)

[0061] The raw material charge composition is Li4P 0.7 Si 0.3 S 3.7 Cl 0.3 I, except for this, the same implementation as in Example 1 is carried out.

[0062] (Example 4)

[0063] The raw material charge composition is Li4P 0.8 Si 0.2 S 3.8 Br 0.2 I, except for this, the same implementation as in Example 1.

[0064] (Example 5)

[0065] The raw material charge composition is Li4P 0.8 Si 0.2 S 3.8 I 1.2 , except for this, the same implementation as Example 1 is carried out.

[0066] (Example 6)

[0067] The raw material charge composition is Li4P 0.8 Si 0.2 S 3.8 Cl 0.1 Br 0.1 I, except for this, the same method as in Example 1 was used. Thus, a Li4P 0.8 Si 0.2 S 3.8 Cl 0.1 Br 0.1 A sulfide-based solid electrolyte having a composition of I.

[0068] (Comparative Example 1)

[0069] The same procedures as in Example 1 were carried out except that the raw material charge composition was Li4PS4I.

[0070] (Comparative Example 2)

[0071] The raw material charge composition is Li4PS 3.8 Cl 0.2 I, except for this, the same implementation as in Example 1 is carried out.

[0072] (Comparative Example 3)

[0073] The raw material charge composition is Li4PS 3.8 Br 0.2 I, except for this, the same implementation as in Example 1.

[0074] (Comparative Example 4)

[0075] The raw material charge composition is Li4P 0.6 Si 0.4 S 3.6 Cl 0.4 I, except for this, the same implementation as in Example 1.

[0076] (Comparative Example 5)

[0077] The raw material charge composition is Li4P 0.95 Si 0.05 S 3.95 Cl 0.05 I, except for this, the same implementation as in Example 1.

[0078] <Composition Analysis>

[0079] 0.5 g of the sample (powder) of each sulfide-based solid electrolyte obtained in Examples 1 to 6 and Comparative Examples 1 to 5 was weighed, dissolved using various acids, and then analyzed for composition using an inductively coupled plasma optical emission spectrometer (ICP-OES) "PS7800" manufactured by Hitachi High-Technologies Corporation. The composition formulas of the sulfide-based solid electrolytes of Examples 1 to 6 and Comparative Examples 1 to 5 obtained by the composition analysis are shown in Table 1.

[0080] <Ion conductivity>

[0081] After 0.2 g of the powder of each sulfide-based solid electrolyte obtained in Examples 1 to 6 and Comparative Examples 1 to 5 was pressed at a pressure of 370 MPa to form a plate, 0.1 g of gold powder was spread on each side and pressed at 555 MPa to produce particles with a diameter of 10 mm and a gold electrode. Using the particles, an applied voltage of 100 mV was set at 30°C, and an E4990A manufactured by TOYO Technica Co., Ltd. with open-circuit-short-circuit correction was used to perform an AC impedance measurement of 20 Hz to 100 MHz. The arc observed in the portion with a frequency of more than 10 kHz of the Cole plot obtained by the AC impedance measurement was analyzed to determine the transfer resistance of Li ions. Next, based on the following formula, the ionic conductivity was determined from the transfer resistance of the Li ions and the thickness and area of ​​the solid electrolyte portion of the particles used in the measurement.

[0082] Ionic conductivity (mS / cm) = thickness of the solid electrolyte part of the particle (cm) × 1000 / [(Li ion transfer resistance (Ω)) × (area of ​​the solid electrolyte part of the particle (cm) 2 ))]

[0083] Table 1 shows the test results.

[0084] [Table 1]

[0085]

[0086] (Evaluation results)

[0087] The sulfide-based solid electrolytes of Examples 1 to 6 all have a composition formula of: Li4P 1-x Si x S 4-x Ha x I (where Ha is any one or two of Cl, Br and I, 0.05<x≤0.3). Therefore, the sulfide-based solid electrolytes of Examples 1 to 6 have an ion conductivity that is up to 10 times higher than that of the conventional sulfide-based solid electrolytes having a Li4PS4I structure. Therefore, the all-solid-state lithium-ion battery using the sulfide-based solid electrolytes of Examples 1 to 6 can be expected to have an improved battery capacity.

[0088] On the other hand, Comparative Examples 1 to 5 do not have the above-mentioned composition and have inferior ion conductivity compared with Examples 1 to 6.

Claims

1. A sulfide-based solid electrolyte having a composition formula: Li4P 1-x Si x S 4-x Ha x I means, In the formula, Ha is any one or two of Cl, Br and I, and 0.05<x≤0.

3.

2. The sulfide-based solid electrolyte according to claim 1, wherein In the above formula, 0.1≤x≤0.

3.

3. An all-solid-state lithium-ion battery, wherein: include: A solid electrolyte layer comprising the sulfide-based solid electrolyte according to claim 1 or 2, a positive electrode layer, and a negative electrode layer.